2020
DOI: 10.1080/09506608.2020.1830665
|View full text |Cite
|
Sign up to set email alerts
|

Confinement effects on compressive and ballistic performance of ceramics: a review

Abstract: Ceramic materials have been extensively used as armour materials for nearly 50 years and continue to attract great interest in the field of defense technology. As confinement is crucial for ceramics to achieve enhanced performance, it has become indispensable in ceramic armour systems. This review aims to explore the effects of a wide variety of confinement on ceramic performance, so as to provide scientific insights for further exploration and development of ceramic materials and ceramic-based armour systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 156 publications
0
9
0
Order By: Relevance
“…The load distribution of the ceramic tiles during the anti-penetration process changes due to the UHMWPE laminate, which results in a wider range of circumferential cracks on the top of the fracture cone than the reference target without UHMWPE laminate, as shown in Figure 14 . Larger circumferential cracks can not only increase the absorbed projectile energy by expanding the crushing range of the ceramic tiles but also prolong the residence time of the projectile on the ceramic surface [ 39 ], which explains that the ceramic tiles in the T-X developed penetrating damage later, as shown in Figure 13 .…”
Section: Numerical Analysismentioning
confidence: 99%
“…The load distribution of the ceramic tiles during the anti-penetration process changes due to the UHMWPE laminate, which results in a wider range of circumferential cracks on the top of the fracture cone than the reference target without UHMWPE laminate, as shown in Figure 14 . Larger circumferential cracks can not only increase the absorbed projectile energy by expanding the crushing range of the ceramic tiles but also prolong the residence time of the projectile on the ceramic surface [ 39 ], which explains that the ceramic tiles in the T-X developed penetrating damage later, as shown in Figure 13 .…”
Section: Numerical Analysismentioning
confidence: 99%
“…The composite target was fixed in a steel frame with a covering plate, with an exposed area of 150 mm × 150 mm. Studies 21,[25][26][27] have shown that lateral constraint and prestress had an important effect on the performance of ballistic ceramics. In order to avoid the interference of above factors on the test results, as shown in Figure 4A, there was an above 3 mm gap between the ceramic side surface and the inner wall of the steel frame, which was filled with expandable polyethylene.…”
Section: Ballistic Testmentioning
confidence: 99%
“…As this point it is also worth to note that under high stress level ceramics may change their fracture character to a more ductile fashion which is the general idea behind modeling them with viscosity-embedded constitutive formalism [36,37]. In particular, beyond a compressive pressure limit, armor ceramics posses a ductile behivour which definitely enhances their energy absorbing limit up to fracture which could also be termed as confinement-induced brittle to ductile transition [38]. High caliber ammunition can impact the target at a speed of approximately 900-1000 m s −1 .…”
Section: Introductionmentioning
confidence: 99%